2013
DOI: 10.1016/j.hcmf.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Performance Measures for the Evaluation of Patients Referred to the Toronto General Hospital's Kidney Transplant Program

Abstract: Given the increasing number of patients with end-stage renal disease in Ontario, there is a need to improve the efficiency and effectiveness of the pretransplant evaluation, to allow for a seamless progression through the various steps in the process. Toronto General Hospital's kidney transplant program is evaluating various performance measures, specifically looking at waiting times from referral to initial evaluation and initial evaluation to final disposition, to use as metrics for monitoring program perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…[62] Likewise, Sultan and colleagues found that the delay in the pre-transplant process is mainly due to the workup being conducted at their local dialysis centres which may not be familiar with the pre-requisite testing resulting in longer waiting time for RT. [63] While addressing these barriers at the hospitals, key-informants suggested that an integrated system for RT service be arranged by coordinating with other supporting services to enhance the pre-transplant evaluation. As the central hub for RT, it would be an appropriate institution to engage experienced surgeons from private practice to train more transplant surgeons in the country.…”
Section: Discussionmentioning
confidence: 99%
“…[62] Likewise, Sultan and colleagues found that the delay in the pre-transplant process is mainly due to the workup being conducted at their local dialysis centres which may not be familiar with the pre-requisite testing resulting in longer waiting time for RT. [63] While addressing these barriers at the hospitals, key-informants suggested that an integrated system for RT service be arranged by coordinating with other supporting services to enhance the pre-transplant evaluation. As the central hub for RT, it would be an appropriate institution to engage experienced surgeons from private practice to train more transplant surgeons in the country.…”
Section: Discussionmentioning
confidence: 99%
“…18 Unplanned return to the operating room 18,24,25,30,36,39,70 was reported in 7 unique publications, and an additional 3 metrics (blood pressure, graft function, and hemoglobin concentration) [77][78][79][80][81][82][83] were also reported in 7 publications, however, these were consecutive annual reports from the same agency rather than unique citations. The other commonly reported quality metrics included the following: waitlist mortality (n = 6 publications), 19,24,27,31,33,35 patient satisfaction (n = 5 publications), 24,30,35,47,48 the wait time from initial evaluation to final disposition (n = 5 publications), [18][19][20][21][22] in-hospital mortality (n = 4 publications), 45,46,51,52 acute graft rejection (n = 4 publications), 39,42,51,52 and infections (n = 4 publications). 24,25,42,51 Types of Quality Metrics…”
Section: Frequency Of Metric Reportingmentioning
confidence: 99%
“…The production of high-quality clinical research is another area of achievement for the UHN KTP following the launch of CoReTRIS. [11][12][13][14] A comprehensive data system housing numerous data domains of interest to healthcare staff from various disciplines has made possible the completion of several health quality and research projects. Such successes are instrumental in positioning the KTP as a centre of excellence in transplant care and research for years to come.…”
Section: Program Quality Initiatives and Scientific Researchmentioning
confidence: 99%